An Android Based Public Submission System for Waste Collection in Indian Cities - Thirupathi Rao, N.; Bhattacharyya, Debnath; Kim, Tai-Hoon (International Journal of Engineering and Technology, 2019)
India is a very populated country and the people in the country are increasing in number by day to day. As the number of the public is going increasing from time to time, the place and the surroundings of the people are filled with more amounts of dust and waste. And it is increasing with the number of people in the country from time to time. Maintaining cleanliness in the city gives the public with good health. If it is not cleaned, the people may get affected by various diseases during especially in rainy seasons. In order to maintain such things, the proper allocation of manpower for cleaning and performing such tasks is going to increase. Hence, an attempt has been made to make the collection of the presence of waste at various locations in the cities filled with more people was tried by developing a mobile application. As the application was a mobile application, it may reach to most of the people in the city. Garbage Management Systems by municipal corporations and other organizations face several problems in locating garbage, monitoring and assigning the work for recycling the garbage. An Android Based Public Submission System for Waste Collection is an Android application which is proposed to minimize these problems and monitor the cleaning activities in and around the cities for the safe and health consciousness of the public in cities.Â